Regulatory challenges and policy strategies for stem cell-based cosmetics in Indonesia - Kashuri, Mohamad (Universitas Muhammadiyah Magelang, 2025)
Introduction: Stem cell-based cosmetics are gaining popularity in Indonesia due to their regenerative and anti-aging properties. However, these products are still governed under a general cosmetic notification system that lacks specific provisions for efficacy validation, safety evaluation, and ethical oversight. The absence of clear regulations may pose significant risks to consumer safety and undermine the credibility of cosmetic biotechnology innovations. Therefore, this study aims to critically analyze the current regulatory landscape surrounding stem cell-based cosmetics in Indonesia, identify key policy gaps, and propose strategic recommendations for establishing a more robust, ethical, and science-based regulatory framework Method: This study employed a narrative literature review approach, analyzing 28 peer-reviewed and open-access publications published between 2020 and 2025. The sources include scientific journals, national regulatory documents, and institutional policy papers that discuss the application of stem cells in cosmetics and their governance within public health frameworks. Results: The review reveals that Indonesia does not yet have a distinct regulatory classification for biotechnology-based cosmetic products. There is no requirement for pre-market efficacy testing or for the disclosure of stem cell origin and processing. In contrast, countries such as South Korea and the European Union have implemented comprehensive regulatory frameworks that ensure transparency, product safety, and ethical compliance. Discussion: The findings indicate that Indonesia’s current passive regulatory approach may compromise consumer protection and fail to respond effectively to emerging biotechnological trends. To close these regulatory gaps, the study proposes the establishment of a specific category for stem cell-based cosmetics, the enforcement of mandatory safety and efficacy evaluations, and the creation of a scientific advisory board to align national regulations with international standards and best practices.